2021
DOI: 10.15295/bmij.v9i3.1838
|View full text |Cite
|
Sign up to set email alerts
|

The effects of economic anxiety on affective occupational commitment: The mediating role of emotional exhaustion

Abstract: This study aims to examine whether emotional exhaustion has a mediating role in the effect of economic anxiety of tour guides on their affective occupational commitment. The research sample included 370 tour guides in Turkey. The data were collected through the questionnaire method. The collected data were analyzed using the IBM SPSS 22 and Process v3.3 macro extension. The mediating role of emotional exhaustion between economic anxiety and affective occupational commitment was calculated via the Bootstrapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Cheng and Yang’s (2018) research also found support for the claim that POS was a remedy to hotel workers’ burnout. A review of the literature demonstrates only one empirical piece reporting a positive association between economic anxiety and occupational commitment (Benligiray and Yetgin, 2021). However, it seems that there is no evidence appertaining to the link between POS and financial anxiety.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng and Yang’s (2018) research also found support for the claim that POS was a remedy to hotel workers’ burnout. A review of the literature demonstrates only one empirical piece reporting a positive association between economic anxiety and occupational commitment (Benligiray and Yetgin, 2021). However, it seems that there is no evidence appertaining to the link between POS and financial anxiety.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Ascertaining the potential remedies to financial anxiety is critical because workers suffer from financial anxiety due to the future uncertainties and current adverse global economic conditions resulting from rising inflation rates in developed and developing countries, as well as the pandemic (cf. Benligiray and Yetgin, 2021; Vieira et al , 2021). More importantly, we do not know whether POS is linked to career commitment via financial anxiety, either.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%